Risk-Based Evaluation of Turkish Agricultural Strategies using Fuzzy AHP and Fuzzy ANP - Demirel, Nihan Cetin; Yucenur, G. Nilay; Demirel, Tufan; Musdal, Hande (TAYLOR & FRANCIS INC, 2012)
In this article, we propose a model for selection of an agricultural strategy for Turkey by using fuzzy analytical hierarchy process (AHP) and analytical network process (ANP) based on linguistic terms. Fuzzy AHP-based methodology will be discussed to tackle the different decision criteria such as risk factors, ecological structure, socioeconomic structure, and technological structure involved in the selection of an agricultural strategy for Turkey and ANP will represent an effective tool for providing a suitable solution for managers and government administrators of this case. The linguistic levels of comparisons produced by the experts for each comparison are tapped in the form of triangular fuzzy numbers in order to construct fuzzy pairwise comparison matrices. The implementation of the system is demonstrated by a problem having four stages of hierarchy that contains 4 criteria and 15 sub-criteria.
Keywords: agricultural strategies for Turkey; fuzzy set; AHP; ANP; risk factors; ANALYTIC NETWORK PROCESS; EXTENT ANALYSIS METHOD; MULTICRITERIA EVALUATION; HIERARCHY PROCESS; DECISION-MAKING; SELECTION; Biodiversity & Conservation; Environmental Sciences & Ecology